Advancing the integration of hospital IT - Engelmann, Carsten; Ametowobla, Dzifa (Applied Clinical Informatics, 2017)
Background: Planning and controlling surgical operations hugely impacts upon productivity, patient safety, and surgeons’ careers. Established, specialized software for this task is being increasingly replaced by “Operating Room (OR)-modules” appended to enterprise-wide resource planning (ERP) systems. As a result, usability problems are re-emerging and require developers’ attention.Objective: Systematic evaluation of the functionality and social repercussions of a global, market-leading IT business control system (SAP R3, Germany), adapted for real-time OR process steering.Methods: Field study involving document analyses, interviews, and a 73-item survey addressed to 77 qualified (> 1-year system experience) senior planning executives (end users; “planners”) working in surgical departments of university hospitals.Results: Planners reported that 57% of electronic operation requests contained contradictory information. Key screens contained clinically irrelevant areas (36 +/− 29%). Compared to the legacy system, users reported either no improvements or worse performance, in regard to co-ordination of OR stakeholders, intra-day program changes, and safety. Planners concluded that the ERP-planning module was “non-intuitive” (66%), increased planning work (56%, p=0.002), and did not impact upon either organizational mishap spectrum or frequency. Interviews evidenced intra-institutional power shifts due to increased system complexity. Planners resented e.g. a trend towards increased personal culpability for mishap.Conclusions: Highly complex enterprise system extensions may not be directly suited to specific process steering tasks in a high risk/low error-environment like the OR.In view of surgeons’ high primary task load, the repeated call for simpler IT is an imperative for ERP extensions. System design should consider a) that current OR IT suffers from an input limitation regarding planning-relevant real-time data, and b) that there are social processes that strongly affect planning and particularly ERP use beyond algorithms.Real improvement of clinical IT tools requires their independent evaluation according to standards developed for pharmaceutical subjects.Citation: Engelmann C, Ametowobla D. Advancing the integration of hospital IT: pitfalls and perspectives when replacing specialized software for high-risk environments with enterprise system extensions. Appl Clin Inform 2017; 8: 515–528 https://doi.org/10.4338/ACI-2016-06-RA-0100
Keywords: Process steering software; surgery; operation room list; enterprise systems; user interface